Penerapan Metode SAW Dalam SPK Untuk Menentukan Masyarakat Yang Layak Mendapatkan Bantuan BLT (Studi Kasus: Masyarakat Kecamatan Kuranji Kota Padang) - Rita; Guslendra (Jurnal Sains Informatika Terapan, 2024)
Providing Direct Cash Assistance (BLT) in Kuranji District, Padang City, is still done manually, which can result in inaccurate decisions and take a long time, so that assistance is often not on target. The solution to this problem is to use a decision support system with the Simple Additive Weighting (SAW) method. The SAW method is a weighted addition that produces accurate ranking decisions. The design of this SPK application uses the PHP programming language and MySQL database, which can process data quickly and accurately for making decisions on the feasibility of receiving BLT in Kuranji District, Padang City. By implementing the SAW method, the process of determining the eligibility of BLT recipients becomes faster and more accurate. The research results show that people who are worthy of receiving BLT are those who have the five highest scores in the ranking, while those ranked below five are considered not worthy of receiving assistance. Based on the values produced by the calculation and ranking of the SAW method, this can be a reference in determining BLT recipients at the Kuranji District Head Office, Padang City. The use of the PHP programming language and MySQL database in this system supports the performance of the Kuranji District Head's Office in managing BLT recipient criteria data and storing BLT data safely, minimizing the risk of data loss.